La automatización robótica de procesos y su relación con la operatividad de los procesos contables en las empresas de telecomunicaciones y banca en los países de Argentina, Chile, Colombia y Perú en el año 2021 - Larios Soldevilla, Omar Alexis (2023)
The objective of this article is to determine the relationship between Robotic Process Automation RPA, with the operation of accounting processes, it also seeks to determine how, (i) the identification of processes to automate, (ii) the automation of the process already implemented, and (iii) the staff training in automation, are related to the efficiency of the accounting processes in the Banking and Telecommunications companies of Argentina, Chile, Colombia and Peru in the year 2021. The theoretical model is based on the review of the literature related to the present investigation, where previous investigations stand out. It is based on the hypothesis that Robotic Process Automation has a positive relationship with the operability of accounting processes in the companies and countries mentioned above. The methodology used includes the bibliographical review of various investigations indexed in the main repositories of the last 6 years, taking in consideration the inclusion and exclusion criteria in topics related to Robotic Process Automation and the different accounting fields. Also, 74 surveys have been carried out on professionals who have implemented RPA in various companies in the Top 10 Banking and Telecommunications sectors in the mentioned countries, in order to verify how this technology has impacted South America. The professionals surveyed have developed RPA in one or two sectors, as well as in one or more of the countries mentioned. Of the surveys carried out, 62 companies have been reached, representing 100% of all companies in the sectors and countries indicated above (Fitch Solutions, 2021a, p. 21; 2021b, p. 31; 2021c, p. 21; 2021d, p. 31; 2021e, p. 21; 2021f, p. 32; 2021g, p. 20; 2021h, p. 31). The results obtained indicate that there is a positive relationship in most of the companies surveyed. The motivation of this research is the dissemination of technological knowledge and its influence, trends and changes in the Accounting career. It is important to mention that the purpose of this research is to provide originality for the study of this tool in the South American region.